(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
It is been observed and evident by many scholars around the world that today 50% of the world population lives in urban centres. The study of population growth rate indicates that if this growth rate continues in the same way at the end of this century almost all the people in the world will live in large cities. All the cities face problems in terms of managing solid waste, scarcity of resources, traffic congestion, air pollution, and inadequate and deteriorating infrastructure. Looking at the urgency to answer such issues many cities have accepted to grow with the idea of being smart. Thus, planning smart cities is a new approach to mitigate the issues created in the urban areas developing with high population growth and concentration of the population. This paper aims to study the smart city concept globally as well as in the context of India and discusses the recommendations that can be carried forward to build smart cities in India.